Histopathology of non-IBD colitis practical recommendations from pathologists of IG-IBD Group. Issue 8 (August 2021) - Reggiani Bonetti, Luca; Leoncini, Giuseppe; Daperno, Marco; Principi, Maria Beatrice; Baronchelli, Carla; Manenti, Stefania; Caprioli, Flavio; Armuzzi, Alessandro; Caputo, Alessandro; Parente, Paola; Cadei, Moris; Villanacci, Vincenzo
Abstract: Pathologists are often called upon to diagnose colitides that differ from the two main forms of inflammatory bowel disease (IBD). These non-IBD colitides include infectious colitis, microscopic colitis, ischemic colitis, eosinophilic colitis, autoimmune enterocolitis, segmental colitis associated with diverticulosis, drug-induced colitis, radiation colitis and diversion colitis. The diagnosis of these different disease entities relies on the histopathological examination of endoscopic biopsies of the gastrointestinal tract. This paper reviews the main histomorphological characteristics of the various Non-IBD colitides.